More or Less Unmarried. The Impact of Legal Settings of Cohabitation on Labour Market Outcomes - Marion Goussé; Marion Leturcq (Institute of Labor Economics (IZA), 2021)
We study how different levels of protection upon separation affect the labour market behaviour of unmarried cohabiting partners. In Canada, unmarried cohabitation becomes a legal status after one year of relationship. Most provinces automatically expand couples' rights and responsibilities after several years of cohabitation: some provinces allow cohabiting partners to claim for alimony upon separation, while others consider cohabiting couples to be equal to married couples. Using cross-province variations in legal settings and minimum eligibility duration, we show that eligibility for a more protective regime increases men's labour supply and earnings and decreases those of women's. The impact of the marriage-like regime is stronger, especially for women. We find that the effect is significantly stronger for couples directly eligible at the time of the reform than for couples who are eligible after the reform and may have anticipated changes in the legal settings. Our results show that eligibility affects within-household allocation of earnings and hours of work, and reinforces existing inequality. We present some evidence that enhancing protection upon separation has an effect on the selection of couples into cohabitation. Our results contribute to the ongoing public debate regarding the legal recognition and level of protection that should be given to unmarried cohabiting partners. Our results show that behavioural response may offset additional protection upon separation by increasing women's dependence on their partner.
Keywords: J12; J22; J18; K36; 330; alimony rights; unmarried cohabitation; labour supply; common law marriage